04.05 The metabolic checkpoint kinase mtor regulates the rheumatoid mesenchymal tissue response to inflammation. (1st March 2017) - Karonitsch, Thomas; Kandasamy, Richard Kumaran; Herdy, Barbara; Dalwigk, Karolina; Niederreiter, Birgit; Holinka, Johannes; Sevelda, Florian; Windhager, Reinhard; Bilban, Martin; Weichhart, Thomas; Säemann, Marcus; Pap, Thomas; et al.
Abstract : Background: By producing cytokines, chemokines and other inflammatory factors fibroblast-like synoviocytes (FLS) frame a microenvironemt that significantly contributes to persistent synovial inflammation in rheumatoid arthritis (RA). The molecular mechanisms and pathways that regulate these responses within FLS are, however, insufficiently explored. Since mTOR is emerging as a regulator of tissue homeostasis that coordinates the cellular reponse to environmental stress, such as inflammation, we hypothesised that this kinase might also determine the FLS response to inflammation. Material and methods: mTOR activation was assessed by immunhistochemistry and western blots. For functional in-vitro studies RA-FLS were stimulated with TNF and specific mTOR inhibitors (Torin-1, PP242 and rapamycin) were applied. Affymetrix microarrays were used for gene expression profiling. NF-κB and STAT1 pathway activation was assessed by western-blots and EMSA. Results: Immunohistochemistry revealed increased mTOR activity in RA synovitis when compared to osteoarthritis. TNF stimulation of FLS ex vivo promoted the phosphorylation of mTOR in an AKT-dependent manner indicating that the pro-inflammatory synovial milieu may drive mTOR activation in RA. Gene expression profiling revealed a so far unknown role for mTOR in the regulation of TNF-induced gene programs: mTOR activation limits the TNF-induced expression of NF-κB-regulated genes (eg, IL6, IL8, PTGS2) by promoting the re-appearence of the NF-κB-inhibitor IκB-α. Contrary, mTOR activation augments the TNF-mediated induction of interferon regulated genes (IRGs; eg, CXCL11, TNFSF13B) by increasing the activity of the transcription factor STAT1. Conclusions: The metabolic checkpoint kinase mTOR fine-tunes the induced gene expression program in FLS. Thus, mTOR emerges as crucial factor for the development of the RA-typical synovial, inflammatory microenvironment.